1996
DOI: 10.1016/0168-9002(95)01517-5
|View full text |Cite
|
Sign up to set email alerts
|

On the electromagnetic energy resolution of Cherenkov-fiber calorimeters

Abstract: Electromagnetic calorimeters which sample the Cherenkov radiation of shower particles in optical bers operate in a markedly dierent manner from calorimeters which rely on the dE/dx of shower particles. The well-understood physics of electromagnetic shower development is applied to the case of Cherenkov-ber calorimetry (also known as quartz ber calorimetry) and the results of systematically performed studies are considered in detail to derive an understanding of the critical parameters involved in energy measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Studies of the Cerenkov/fiber sampling technique with electrons [8] and have been reported elsewhere. One device [5] was built and operated in a fixed target experiment.…”
Section: Discussionmentioning
confidence: 99%